SUBSTITUTION OF ROOTS WITH SMALL BRANCHES OF RAUWOLFIA SERPENTINA FOR THERAPEUTIC USES - A PHYTOCHEMICAL APPROACH (AYUSHDHARA, 2016)
Rauwolfia serpentina commonly called Sarpagandha is a medicinal plant widely used in Ayurveda. As per the Ayurvedic literature, roots of this plant are used in cardiac disorder, cancer, mental illness and psychiatric disorder. To collect roots for medicinal purpose whole plant is uprooted on a mass scale from their natural habitat which is leading to depletion of resources, due to which plant may be difficult in near future for use in traditional systems of medicine. Present study was carried out to assess possibilities of using small branches of R. serpentina in place of its roots which will help in conservation of this plant and availability of raw material for therapeutic purposes. Roots and small branches of R. serpentina are compared on the basis of physicochemical analysis, phytochemical analysis, total phenolic contents, total flavonoid contents and high performance thin layer chromatography (HPTLC) to evaluate the possibilities of using small branches in place of its roots. Results of phytochemical analysis and HPTLC of n-hexane, ethyl acetate and ethanol extracts showed many similarities whichsuggest that small branches may have nearly similar active constituents like roots and may be used as a substitute of roots after comparison and confirmation of same for pharmacological activities.